Socio-Cultural Values as Community Local Wisdom Katoba Muna in the Development of Learning Materials Social Studies and History - Bauto, Laode Monto (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2013)
Katoba culture as one form of local wisdom Muna society contains many positive values that need to be preserved and developed. The positive values include religious, social, political, economic, and historical values. This study addressed the relating socio-cultural values learning with appropriate conceptual of Social Science for Elementary school curriculum. Because one of the goals of this study is to develop learning materials Social Science- Elementary school to enhance students' knowledge, attitudes, and skills against local culture (Katoba) to master the subject matter of Social Science- Elementary school. Therefore, the development learning materials will be integrated with relevant local cultural values. The relevant local cultural values (Katoba) curriculum of Social Science- Elementary school is the social values, culture, economics, politics/history, and art/creativity and religion. In addition, the integration of social values in learning katoba cultural, Social Science through cooperative approaches with clarification in terms of the value of learning according to permendiknas No. 41/2007-the model is relevant to theories of learning, and the learning model is selected. Through the stages of Social Science learning model development that are expected to improve the study results (koginitif), strengthen the appreciation and attitude of the students towards the local culture (katoba). This emphasis on the learners' learning process through reconstruction, finding, acquiring knowledge, and developing social values of cultural katoba that is believed or understood and served as a pattern of behavior guidelines in social life. The learning process aligns with emphasizing the outstanding character education of self-reliant humans (moral autonomy) in a neighborhood, community, nation, and state.